2003
DOI: 10.1353/psc.2003.0033
|View full text |Cite
|
Sign up to set email alerts
|

Nesting Behavior of Palila, as Assessed from Video Recordings

Abstract: We quantified nesting behavior of Palila (Loxioides bailleui), an endangered Hawaiian honeycreeper, by recording at nests during three breeding seasons using a black-and-white video camera connected to a videocassette recorder. A total of seven nests was observed. We measured the following factors for daylight hours: percentage of time the female was on the nest (attendance), length of attendance bouts by the female, length of nest recesses, and adult provisioning rates. Comparisons were made between three sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In another instance in Pōhākea in 2015, a cat killed birds at 15% of all monitored burrows over a couple of weeks; this same cat subsequently raised a litter of kittens in 1 of the Newell's shearwater burrows where it had killed both adults, and we saw the cat on camera later in the season bringing its kittens to other active burrows to hunt birds. Cats have been identified as a key predator of other native bird species, including forest birds such as the endangered Palila ( Loxioides bailleui ; Laut et al 2003) and waterbirds such as the Hawaiian moorhen ( Gallinula galeata sandvicensis ), Hawaiian duck ( Anas wyvilliana ), nēnē ( Branta sandvicensis ), and Hawaiian coot ( Fulica alai ; Baker et al 2019). Cat control is an effective conservation tool for seabirds in other parts of the world (Cooper et al 1994, Nogales et al 2004, Bellingham et al 2010, Rauzon et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In another instance in Pōhākea in 2015, a cat killed birds at 15% of all monitored burrows over a couple of weeks; this same cat subsequently raised a litter of kittens in 1 of the Newell's shearwater burrows where it had killed both adults, and we saw the cat on camera later in the season bringing its kittens to other active burrows to hunt birds. Cats have been identified as a key predator of other native bird species, including forest birds such as the endangered Palila ( Loxioides bailleui ; Laut et al 2003) and waterbirds such as the Hawaiian moorhen ( Gallinula galeata sandvicensis ), Hawaiian duck ( Anas wyvilliana ), nēnē ( Branta sandvicensis ), and Hawaiian coot ( Fulica alai ; Baker et al 2019). Cat control is an effective conservation tool for seabirds in other parts of the world (Cooper et al 1994, Nogales et al 2004, Bellingham et al 2010, Rauzon et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Videographic evidence of predation by cats on endangered species has confirmed that cats do not merely scavenge carcasses of dead birds, but depredate live birds, particularly nestlings. On Mauna Kea, four occasions of depredation have been recorded on endangered palila (Loxioides bailleui) nestlings, a forest-dwelling finch-billed honeycreeper that nests in woodland tree canopies (Laut et al 2003, Lindsey et al 2009). An estimated 11% of palila nests are depredated annually by feral cats (Hess et al 2004).…”
Section: Lines Of Evidence Diet and Predationmentioning
confidence: 99%
“…Hundreds of vertebrate prey species have been found in studies of cat diets throughout islands of the world , and recent videographic studies have confirmed that cats do not merely scavenge the carcasses of dead birds; they depredate live birds, often endangered species (Laut et al 2003, Lindsey et al 2009). Insular prey are particularly vulnerable because of life history characteristics that confer island naïveté; however, habitat fragmentation in continental areas may also confer vulnerability to prey species (van Heezik et al 2010).…”
Section: Conclusion Cats and The Club Med Syndromementioning
confidence: 99%
“…They were subsequently reported to be notorious and harmful predators that contributed to the decline and extinction of some Hawaiian bird species (Perkins 1903, Ralph and van Riper 1985, Stone 1985, Smucker et al 2000. Feral cats in Hawai'i prey upon endangered forest birds (Laut et al 2003, Hess et al 2004) and terrestrial birds that nest near the ground (Kowalsky et al 2002), as well as colonial nesting seabirds (Hu et al 2001, Smith et al 2002). In addition, cats are the definitive host of Toxoplasma gondii, a parasite that has killed individuals of several native and introduced wildlife species (Work et al 2000, Honnold et al 2005.…”
mentioning
confidence: 99%